Relationships between leadership behaviour of nurse managers and nurses' levels of job satisfaction and compassion fatigue during the COVID‐19 pandemic - Gulcan Taskiran Eskici; Ece Uysal Kasap; Emel Gumus (Wiley, 2023)
Abstract Aim To reveal the relationships between the leadership behaviour of nurse managers and nurses' levels of job satisfaction and compassion fatigue during the COVID‐19 pandemic. Design and Methods This descriptive and cross‐sectional study was performed with 353 nurse professionals participating from 32 cities across Turkey. The data were collected online between August and November 2020 by using the introductory information form, Minnesota Satisfaction Questionnaire, Leadership Behaviour Questionnaire and Compassion Fatigue subdimension of the Professional Quality of Life Scale. The Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines were followed in the study. Results Nurses mostly stated their managers as employee‐oriented and change‐oriented leaders. Nurses' intrinsic and overall satisfaction was high, extrinsic satisfaction was low and their compassion fatigue was at a critical level during the pandemic. According to nurses' personal and professional characteristics, there were significant differences in job satisfaction, compassion fatigue and change‐oriented leadership scores. When nurse managers exhibit employee‐oriented leadership behaviour, nurses' compassion fatigue decreases and job satisfaction increases.